The Concept of Organic Cultivation as a Sustainable Agricultural Education Effort - Hening Widowati, Agus Sutanto, Achyani, Fenny Thresia, Nedi Hendri, Mia Cholvistaria (International Journal of Advanced Science and Technology, 2020)
Farmers generally prefer non-organic farming. This study examines the residue of active ingredients due to the use of synthetic chemical pesticides. It conducted with organic farming methods that are environmentally friendly by utilizing fermented fertilizers and refugia biopesticides. It was randomly sampled the water, soil, and products of 9 types of vegetables with four replications in the vegetable field of Karangrejo Sub-District, North of Metro Lampung, Indonesia in April-September 2019. The non-organic farmed expose facto data was used as a control. Data were analyzed by means of the different t test, and descriptive by examining laboratory test documents for increasing land productivity and agricultural yields. The results showed that the levels of active residues of chlorfenapyr, diphenoconazole, and low fipronil below the permitted threshold were found in soil, water, and all types of non-organic vegetables, with significantly different residue levels of p ≤ 0.05. While organic management is only found in the soil where vegetables grow, those were not detected. The findings of organic farming are very significantly different for all parameters of active residues, as well as increased productivity of land and agricultural products can be socialized for healthy living and environmentally friendly farming and sustainable agricultural education effort.